Judaísmo, neoplatonismo e cabala : a teoria do amor de Judá Abravanel (Leão Hebreu) nos "Diálogos de Amor" - Gomes, Gilmar Araújo (2017)
Born in Lisbon in an inaccurate date between 1460 and 1470, Judah Abravanel, since young, according to his biographer João Vila-Chã, devoted himself to study, contemplation and the typical teaching and learning model of the outstanding Jewish families of his time, or that is, a model marked by a substantial program of studies which included, in particular, Greek and Hebrew heritage. However, the first characteristic that differentiates his intellectual development is the condition of being the son of Isaac Abravanel (1437-1508), counselor and treasurer of D. Afonso V, whose prominence in the Portuguese court generated disagreements against the actions of the Jews. To his father, his personality is very much obliged; both in their public performance, in the synagogue and in the court, as well as in personal orientations; his father transmitted to him the initiation into the secrets of Kabbalah and the philosophical reflections of authors like Aristotle and Maimonides. Also known as the Leone Ebreo, the study of Judah Abravanel's historical-religious identity, contained in the book Dialogues of Love, proposes a perspective of wandering being-in-exile, ie experiencing the human condition in terms of passion and pain, proper of the sephardic mentality that is strengthened from that period, like dispersed Jew. The poetics present here manifests a theory of love produced with strong influence, among others, by Marsilio Ficino and Jochanan Alemanno, the latter one of the precursors Hebrew of the humanist Pico della Mirandola, and who is said to have provided a meeting between the two. Not only did his Dialogues of Love intertwines the Jewish Scriptures with the teaching of Plato, Aristotle, the Stoics and the Arabs (especially Averroes and Avicenna), but they also influenced the work of later authors such as Giordano Bruno. The Neoplatonic perspective there conceives love as a universal principle, uniting the inferior to the superior, the universe with its creator; moreover, he understands creation as an a priori given, hence "he indulges in the refutation of the Aristotelian thesis of the eternity of the world" (CALAFATE, 2000). The Neoplatonic writing of Judah Abravanel hides a structure of Kabbalah teaching, as learned from the wise Jewish theologians, who would have influenced the philosophy of Plato, as understood by Leone Ebreo. Therefore, this work has as general objective, to expose the conception of love of Judah Abravanel expressed in his Dialogues of Love, emphasizing the literary, philosophical and religious aspects that compose this work.